A Hybrid Schottky–Ohmic Drain Contact for Thermally Stressed Beta‐Gallium Oxide Field‐Effect Transistors. Issue 5 (5th February 2023) - Jeong, Yeong Je; Lee, Chan Ho; Yeom, Min Jae; Yang, Jeong Yong; Yoo, Geonwook
Abstract : Degradation of ohmic contacts on β ‐Ga2 O3 under thermal stress conditions is a severe issue that hinders its high‐temperature applicability. Herein, a hybrid Schottky–ohmic drain contact (HSD) is demonstrated in β ‐Ga2 O3 field‐effect transistors (FETs). It is compared with a conventional ohmic drain contact (OD) after extended thermal annealing. Pulsed drain bias measurement is conducted to investigate the trapping process at the interface of both drain contacts with the β ‐Ga2 O3 channel. Even with the extended Schottky metal region, the β ‐Ga2 O3 FET with the HSD contact exhibits similar contact and on‐resistance. Additionally, it shows field‐effect mobility higher than that of the OD contact device. Enhanced off‐state breakdown characteristics are achieved. Abstract : Herein, a hybrid Schottky–ohmic drain contact (HSD) is demonstrated in β ‐Ga2 O3 field‐effect transistors (FETs). It is compared with a conventional ohmic drain contact (OD) after extended thermal annealing. The off‐state breakdown characteristics of the HSD device are superior to those of the OD device.